A new experimental simulation method for the development of non-renewable hydrogen energy—Oil and gas resources. (26th February 2019) - Tian, Yangyang; Tian, Yu; Qu, Zhanqing; Guo, Tiankui; Shi, Yongmin; Zhang, Liaoyuan
Abstract: At present, the proportion of tight oil in non-renewable hydrogen energy is increasing. According to an initial exploration and attemptable practice on the exploration of tight oil, it is found that the cost can be controlled effectively and positive effects are achieved. But this technique cannot make sure the proppants filled uniformly in the long fracture. Several researches on the proppants migration experiment devices and factors influencing on proppant setting are reviewed and a new set of experimental device to simulate the laws of proppants setting in long fracture is developed. This device can simulate the main factors influencing proppants setting performance. It analyzes several factors such as wall filtration, construction displacement, sand concentration, proppant size and density, viscosity of fracturing fluid is used to rank the influencing degree of every factor. Considering the effects of mutual interference between proppants, width of fracture, rough fracture surface and fracture surface filtration during the proppants setting progress, the mathematical model of proppant setting is modified by adding sand concentration correction factor, wall effect correction factor and filtration correction factor. The experimental data verify the accuracy of the settlement model is established using the data getting from experiment. Highlights: Simulated the factors influencing proppant placement, including wall filtration. The mathematical model of proppant placement is modified by adding filtration correction factor. The influence of different factors on proppant placement is quantitatively analyzed.